Influence of tensile strain on rat mesenchymal stem cell proliferation, differentiation and apoptosis - Kearney, Emma M. (Trinity College (Dublin, Ireland). Department of Physiology, 2008)
Tissue engineering strategies that involve mesenchymal stem cells (MSCs) represent promising developments within regenerative medicine today. However, before MSCs are suitable for use in the clinic, the intricacies of how their remarkable multipotential and proliferative characteristics are controlled must be understood. One of the most potent regulators of MSC fate is biomechanical stimululation. Herein, this research examines the response of MSCs to cyclic mechanical tensile strain, and identifies the intracellular controls involved in these. The research began by characterising both the substrate material and the cell population. Following topographical and mechanical characterisation, collagencoated silicone that was exposed to UV was identified as the optimal surface. Adherent cells isolated from rat bone marrow stroma were characterised as a homogeneous population of cells that express the mesenchymal stem cell markers CD90 and CD105, and demonstrated an osteogenic response following incubation with osteogenic factors.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin